Analisis Pengaruh Influencer Marketing dan Brand Love terhadap Keputusan Pembelian Produk Skincare Skintific - Dhea Nofa Lestiyani; Sugeng Purwanto (BUDGETING : Journal of Business, Management and Accounting, 2023)
This study aims to analyze the effect of influencer marketing and brand love on purchasing decisions for skintific skincare products. This research method is a quantitative method. The hypothesis in this study was tested using the Structural Equation Model, because the SEM model test is an advanced development of multiple regression analysis. The results of this study note that the T-statistic value of influencer marketing on purchasing decisions is 3,348. The test results show that the T-statistic value is > 1.96. The influencer marketing variable on purchasing decisions shows a value of 0.001. The T-statistic value of brand love on purchasing decisions is 2,459. The test results show that the T-statistic value is > 1.96. The brand love variable on purchasing decisions shows a value of 0.014. It can be concluded that influencer marketing and brand love influence purchasing decisions. The R-square value is 0.489 which can be concluded that the purchasing decision variable (Y) can be explained by influencer marketing and brand love variables of 48.9%. While the remaining 51.1% is influenced by other variables. Keywords: Brand Love, Buying Decision, Influencer Marketing, Skincare Skintific.